Radial optic neurotomy for central retinal vein occlusion: Results of the pan-american collaborative retina study group (pacores) (2008)
OBJECTIVE: To evaluate the complications after radial optic neurotomy (RON) for central retinal vein occlusion (CRVO). METHODS: Seventy-three consecutive patients (73 eyes) with CRVO who were treated with RON participated in a retrospective, uncontrolled, interventional, multicenter case series at 7 institutions from 6 countries. RESULTS: In the ischemic CRVO group (n = 53), 32% of eyes had an improvement in best-corrected visual acuity (BCVA) (mean, 5.5 lines), 35.8% had worse BCVA (mean, 6.4 lines), and 32% had BCVA that remained the same after RON. In the nonischemic CRVO group (n = 20), 50% of eyes had an improvement in BCVA (mean, 6.5 lines), 15% had worse BCVA (mean, 4.3 lines), and 35% had BCVA that remained the same after RON. Complications occurred in 71.2% of cases, including cataract in 17 eyes (23.2%), vitreous hemorrhage in 16 eyes (20.5%), persistent macular edema in 15 eyes (20.5%), neovascular glaucoma in 7 eyes (9.5%), anterior segment neovascularization in 5 eyes (6.8%), retinal detachment in 3 eyes (4.1%), and phthisis bulbi, choroidovitreal neovascularization, central retinal artery perforation, and optic nerve atrophy in 1 eye (1.3%) each. CONCLUSIONS: RON may improve visual acuity in some eyes with CRVO, but complications are common. In our series, surgery by itself did not seem to improve the outcome of CRVO when compared with its natural history. Copyright © 2008 by the Ophthalmic Communication Society Inc.